EFEKTIVITAS GASTROPROTEKTIF INFUSA RAMUAN AKAR MANIS (Glycyrrhiza glabra), KULIT BATANG PULASARI (Alyxia reinwardtii Bl) DAN DAUN SEMBUNG (Blumea balsamifera) PADA TIKUS MODEL TUKAK LAMBUNG - , Agustin Wijayanti ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Non steroidal antiinflammatory medicine such as acetosal have been largely used. Itâs adverse reactions include superficial gastric erotion that result in peptic ulcer. Previously, Glycyrrhiza glabra containing glycyrrhizin and Blumea balsamifera containing quersetin, have been proved is ability of gastric mucosa caused by acetosal induction. Empirically, Alyxia reinwardtii contains several active substances of volatile oil and 3-hydroxicumarine. The aim of the study is the infuse of three plants combination in protecting gastric mucosa to look at the score of mucosal number damage, the number on the of mast cell and eosinophil on mice as gastric ulcer model induced by acetosal. This experimental was concucted study used the postâtest only controls group design. Thirty white male Wistar rats of 2-3 month old, of body weight were randomly devided into six groups of five. The first group were AO (acetosal 90 mg/ 200g BB), the second was AIR (sweet roof 54,6 mg/ 200 g BB + pulasari bark of 20 mg/200 g BB + sembung leaf 91,5 mg/200 g BB) , the third was AIS (sweet roof 54,6 mg/ 200 g BB + pulasari bark 40 mg/ 200 g BB + sembung leaf 91,5 mg/ 200 g BB) , the fourth was AIT (sweet roof 54,6 mg/ 200 g BB + pulasari bark 60mg/ 200 g BB + sembung leaf 91,5 mg/ 200 g BB), the fifth was AS (acetosal 90 mg + sucralfat 72 mg /200 g BB), the six was OIS (sweet roof 54,6 mg/ 200 g BB + pulasari 40 mg/ 200 g BB + sembung leaf 91,5 mg/ 200 g BB). All treatments were given per oral during 7 days. Ten minutes after drug treatmen, the mice were induced by acetosal. At the 8 th day, the mice were fasted for 24 hours, and then, they sacrificed. The total and the average of lession area in the gastric mucosa was observed. The gastrohistopathology feature in mice was examined using haematoxiline eosin dying with mucosal lession scorring eosinophil. The total of mast cell staining by toluidine blue. The non parametric test of Kruskal-Wallis and Mann-Whitney were applied. The combination of sweet roof, pulasari bark and sembung leaf was observed significantly (p<0,05) the lession score. This result also supported by histopatological examinations. The treatment group had a percentage of the number of mast cells and eosinophils were lower than the acetosal group.